2017
DOI: 10.3390/toxins9090270
|View full text |Cite
|
Sign up to set email alerts
|

Spread of Tst–Positive Staphylococcus aureus Strains Belonging to ST30 Clone among Patients and Healthcare Workers in Two Intensive Care Units

Abstract: Staphylococcus aureus is a major cause of infections. Toxic shock syndrome toxin (TSST-1) and Panton–Valentine leukocidin (PVL) are associated with severe clinical syndromes. S. aureus colonizing isolates recovered from healthcare workers and patients in the intensive care unit (ICU) of a university hospital comprising Group A were compared with those from adult non-ICU carriers (Group B). mecA, lukS/lukF-PV (Panton–Valentine leukocidin, PVL), and tst (toxic shock syndrome toxin) gene carriage was detected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…This clone had previously been reported from humans (MSSA and MRSA), feral cat (MRSA) and camel (MSSA) [18,38,39]. ST30 was only recovered from human isolates [40]. The clustered MSSA isolates included in this study demonstrated different clone variations circulating from humans, farm animal and pets.…”
Section: Discussionmentioning
confidence: 50%
“…This clone had previously been reported from humans (MSSA and MRSA), feral cat (MRSA) and camel (MSSA) [18,38,39]. ST30 was only recovered from human isolates [40]. The clustered MSSA isolates included in this study demonstrated different clone variations circulating from humans, farm animal and pets.…”
Section: Discussionmentioning
confidence: 50%
“…Epidemiology of ST types of MRSA strains represents the current Greek epidemiology with the invasion of the community-acquired ST80 clone in the healthcare system supplanting the previous nosocomial clone of ST239 [7,30]. The four infections due to ST30 depict this clone's dissemination among patients and personnel of the ICU [31].…”
Section: Discussionmentioning
confidence: 99%
“…MRSA and MSSA can be considered parameters for the valuation of dedicated food chains: Poultry meats [ 46 ] and sheep (ovine food-chain) [ 47 ]. Specific genomic features, as pvl or mecC, were reported recently as emergent virulence factors in livestock in different papers [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%